The Global Adolescent Girl Agenda: An Analysis of the Emergence and the Political Outcomes of Two Global Health Networks - Noha Shawki (Journal of Social and Development Sciences, 2019)
This article applies the framework developed by the Global Health Advocacy and Policy Project (GHAPP) to analyze the emergence and effectiveness of global health networks to two networks. One of them is Girls Not Brides, a global network of stakeholders working to end child, early, and forced marriage. The other is the network that is working to improve menstrual hygiene management (MHM) in schools and that includes the MHM in Ten network. By providing a theoretically informed account of these two networks, the article contributes to the literature by providing accounts of additional networks that can help us deepen our understanding of the factors that shape transnational network emergence and political outcomes. The two networks in this study complement the case studies completed by the GHAPP because they focus on a complex and politically and culturally sensitive set of issues. Furthermore, this article bridges the gap between the scholarly literature and the literature produced by NGOs and international organizations by providing a theoretically informed account of the effort to end child marriage and improve (MHM) in schools.